ANALISIS POTENSI PEMBERDAYAAN EKONOMI MASYARAKAT BERBASIS MASJID DI KOTA BANDA ACEH - Kamaruddin Kamaruddin (Universitas Islam Negeri Ar-Raniry, 2013)
Mosque-based economic empowerment aims to increase the independence and well-being in which the mosque is expected to meet the financial needs independently and it is instrumental in creating a prosperous society. Economic empowerment of local communities is not limited to business - of producing goods and services but also includes training and mentoring, financing or access to capital and market access. This study examines the potential of mosque in the city of Banda Aceh and also provides an overview of the opportunities and challenges in the community empowerment such as: (i) human resources, (ii) institutional capacity (iii) social integrity (iv) SME business climate and surrounding environment and (v) stakeholders support.